Innovative culture of teachers - part of organisational culture - Lucia Pîrău; Sergiu Baciu (Institute of Social Affairs of the Pedagogical University of Cracow, 2023)
The development of the innovative culture of the teachers will be possible and efficient only if it is based on theoretical and praxiological patterns of their innovative culture. In this context, the scientific issue that follows to be under discussion consists in strengthening the theoretical and praxiological concepts of the teachers' innovative culture development, and the elaboration of a pedagogical model for the development of the teachers' innovative culture that will contribute to a change in education. This thesis is a theoretical study of interdependence and influence of organisational culture on innovative culture. The lack of studies of innovative culture of the teaching staff within a general education establishment has entailed theoretical research of the already existent scientific findings and of the results of the studies made by professionals, particularly, in the sphere of business and entrepreneurship. There has been made a synthesis of the specialised literature concerning the definitions of the concept of organisational culture and types of cultures that would have either a positive, or a negative impact on the values, rules and innovative behaviour within the organisation. The studies provide the triggering factors of innovative culture and preconditions for development and formation of innovative culture, as well as the dimensions of such innovative culture. Keywords: organisational culture, innovative culture, factors and conditions of innovative culture, dimensions of innovative culture Innowacyjna kultura nauczycieli - część kultury organizacyjnej Rozwój kultury innowacyjnej nauczycieli będzie możliwy i skuteczny tylko wtedy, gdy zostanie oparty na teoretycznych i prakseologicznych wzorcach ich kultury innowacyjnej. W tym kontekście następna problematyka naukowa polega na wzmocnieniu teoretycznych i prakseologicznych koncepcji rozwoju kultury innowacyjnej nauczycieli oraz wypracowaniu pedagogicznego modelu rozwoju kultury innowacyjnej nauczycieli, który przyczyni się do zmiany Edukacja. Niniejsza praca jest teoretycznym studium współzależności i wpływu kultury organizacyjnej na kulturę innowacyjną. Brak badań nad kulturą innowacyjną kadry pedagogicznej w placówce szkolnictwa ogólnokształcącego pociągnął za sobą konieczność teoretycznego zbadania dotychczasowego dorobku naukowego oraz wyników badań dokonywanych przez profesjonalistów, zwłaszcza w sferze biznesu i przedsiębiorczości. Dokonano syntezy literatury specjalistycznej dotyczącej definicji pojęcia kultury organizacyjnej oraz rodzajów kultur, które miałyby pozytywny lub negatywny wpływ na wartości, zasady i zachowania innowacyjne w organizacji. W badaniach przedstawiono czynniki wyzwalające kulturę innowacyjną oraz warunki rozwoju i kształtowania się kultury innowacyjnej, a także wymiary tej kultury innowacyjnej.